IMPROVING THE RESULT OF STUDENTS’ LEARNING ON SQUARE AND RECTANGLE MATERY THROUGH COLLABORATIVE LEARNING AT CLASS VII MTS YTPI AL-BUKHARI MUSLIM - Nasution, Nurul Rafiqah (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2023)
This study aims to find out: 1) Students mathematics learning outcomes before and after being taught with collaborative learning at class VII MTs YTPI Al-Bukhari Muslim. 2) Improving students mathematics learning outcomes through collaborative learning at class VII MTs YTPI Al-Bukhari Muslim. 3) The process of learning mathematics through collaborative learning at class VII MTs YTPI Al-Bukhari Muslim MTs. 4) Response of students taught through collaborative learning at class VII MTs YTPI Al-Bukhari Muslim. The research method used is classroom action research with the aim of improving the quality of classroom learning practices and improving the results of mathematics learning. Respondents in this study were seventh grade students of MTs YTPI Al-Bukhari Muslim. The types of data obtained in this study are quantitative data and qualitative data. The results of this study indicate that learning by implementing collaborative learning for the cycle I of 23 students on the test I learning outcomes there are 16 students (69,57%) who achieve mastery learning, while 7 more students (30,43%) have not achieve mastery learning with classical completeness of 69.57%. In the learning outcomes test II for the cycle II has reached as many as 19 students learning completeness (82,61%), while 4 students (17,39%) have not achieved mastery learning with classical completeness of 82,61% to obtain improved learning outcomes mathematics in cycle I and cycle II was 13,04%. This shows that collaborative learning can improve student learning outcomes and student activities and can be used as an alternative to improve student learning interest.